Mengambil Ijarah Berupa Upah dari Pelaksanaan Mengajarkan Al-Qur’an Menurut Imam Asy-Syafi’I dan Imam Ahmad Ibn Hambal (Studi Kasus Masjid Agung Rantauprapat) - Bayu Alfiki; Aripin Marpaung (Raudhah - Proud To Be Professional, 2022)
Ijarah is an action taken by the community to facilitate the utilization of the benefits they get from the work they have done. In another context, ijarah can be interpreted as a rental payment given to individuals who have carried out the work as a reward for their efforts. The focus of this research is to explore the views of Imam Asy-Shafi’i and Imam Ibn Hambal regarding the acceptance of ijarah (wages) in teaching Al-Qur’an activities. The approach used in this study is normative-sociological, based on religious texts such as the Al-Qur’an and Hadith, as well as the opinions of the scholars. The research method used is field research which aims to specifically understand situations that occur in social life. The results of the research show that Imam Asy-Shafi’i believes that taking ijarah (wages) in teaching Al-Qur’an is permissible, because it involves time and knowledge in its implementation. According to Imam Syafi’i, teaching the Qur’an is not an obligatory act of worship. Meanwhile, Imam Ibn Hambal is of the opinion that it is not permissible to take ijarah (wages) in teaching the Qur’an. According to Imam Ibn Hambal, teaching the Qur’an is a manifestation of piety to Allah SWT, where the reward can only be obtained in the form of a reward from Allah alone.